Escape from the Museum of Ethnography: the Right to Culture as the Core of the ECRML - Oszmiańska-Pagett, Aleksandra (Investigationes Linguisticae, 2019)
The aim of this article is to explain the various aspects of the right to culture within the obligations contained in the ECRML. The presentation discusses the issues of cultural products, institutions, participation, linguistic landscape and intangible heritage. Consequently it is clear that the cultural dimension is present across various domains of public life covered by the Charter because its fundamental objective is to foster minority culture as part of life of a community, rather than just an aspect of folklore to be displayed in a museum.